Challenges and [Possible] Solutions to Optimizing Talent Identification and Development in Sport - Till, Kevin; Baker, Joseph (Frontiers in Psychology, 2020)
The modern-day landscape of Olympic and Professional sport is arguably more competitive than ever. One consequence of this is the increased focus on identifying and developing early athletic talent. In this paper, we highlight key challenges associated with talent (athlete) identification and development and propose possible solutions that could be considered by research and practice. The first challenge focuses upon clarifying the purposes of talent identification initiatives such as defining what talent is and how its meaning might evolve over time. Challenge two centres on ways to best identify, select and develop talent, including issues with different approaches to identification, the need to understand the impact of development and the need to have appropriate resourcing in the system to support continued development of knowledge. Finally, we discuss two emerging challenges in relation to the ‘healthiness’ of talent identification and developments that will have important impact on talent identification and development systems. The first examines whether a talent identification and development system be is ‘healthy’ for athletes while the second focuses on how sport stakeholders could discourage the apparent trend towards early specialization in youth sport settings. Whilst this paper discusses the research in relation to these challenges, we propose multiple possible solutions that researchers and practitioners could consider for optimising their approach to talent identification and development. In summary, talent is a complex and largely misunderstood phenomenon lacking robust research evidence, and given concerns that it is potentially unhealthy, talent identification and selection at younger ages is not recommended.